Activity Participation and Perceptions on Informal Public Transport and Bus Rapid Transit in Dar es Salaam. Issue 11 (November 2020) - Joseph, Lucy; Neven, An; Martens, Karel; Kweka, Opportuna; Wets, Geert; Janssens, Davy
This paper seeks to understand participation in out-of-home activities by inhabitants in Dar es Salaam, and their perceptions toward informal public transport (IPT) and bus rapid transit (BRT) in supporting these activities. Without fixed schedules, IPT (e.g., minibuses, motorcycles, and tricycles) is used as a means of transport for different trips. However, IPT is burdened by poor roads, traffic congestion, and high transport demand. Many developing cities are seeking to replace IPT with formal BRT lines. However, little is known in relation to the ability of IPT and BRT to support out-of-home activity participation of the inhabitants. This paper reports on a study in Dar es Salaam exploring the relative contribution of each type of service. The study took place before the opening of BRT, and encompasses focus group discussions, participatory geographical information systems, and questionnaires carried out in two study zones: one close to a BRT corridor and the other in a peri-urban location. The findings show that IPT was used to support participation in daily activities like work, education, shopping, and social matters; and was perceived to be flexible in providing access to both high and low density unplanned settlements. The BRT was viewed to benefit specific groups of people, especially individuals working in permanent offices in and around the city center, particularly professional workers. This paper sheds light on how the two systems were perceived by the local people and can inform policy makers about possible improvements in public transport systems to support activity participation of their inhabitants.